A revision of Late Devonian (Famennian) "thallophyte" (probable Rhodophyte and Phaeophyte) algae from the Witpoort Formation of South Africa - Reddy, Caitlin (Rhodes University, Faculty of Science, Department of Geology)
Access restricted. Expected release in 2026.
Keywords: Uncatalogued